2020
DOI: 10.14569/ijacsa.2020.0110146
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Non-Discriminant ERD/ERS Comprising Motor Imagery Electroencephalography Signals

Abstract: Classification of Motor Imagery (MI) Electroencephalography (EEG) signals has always been an important aspect of Brain Computer Interface (BCI) systems. Event Related Desynchronization (ERD)/ Event Related Synchronization (ERS) plays a significant role in finding discriminant features of MI EEG signals. ERD/ERS is one type and Evoked Potential (EP) is another type of brain response. This study focuses upon the classification of MI EEG signals by Removing Evoked Potential (REP) from non-discriminant MI EEG data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…We found that the weights of the Transformer module corresponding to the sensorimotor areas [48][49][50] showed a pattern of event-related desynchronization (ERD). These data were consistent with the Mu and beta band rhythmic ERD [51,52]. The visualization results demonstrated that Transformer-based methods can contribute to the understanding of network behavior for the classification tasks based on the EEG data.…”
Section: Introductionsupporting
confidence: 77%
“…We found that the weights of the Transformer module corresponding to the sensorimotor areas [48][49][50] showed a pattern of event-related desynchronization (ERD). These data were consistent with the Mu and beta band rhythmic ERD [51,52]. The visualization results demonstrated that Transformer-based methods can contribute to the understanding of network behavior for the classification tasks based on the EEG data.…”
Section: Introductionsupporting
confidence: 77%